2020
DOI: 10.1039/c9cy01585j
|View full text |Cite
|
Sign up to set email alerts
|

Strong Lewis acidic catalysts for C–F bond activation by fluorination of activated γ-Al2O3

Abstract: A strong solid Lewis acid catalyst has been successfully obtained by modifying a known procedure of fluorinating γ-aluminium oxide, which was pre-calcined under vacuum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 69 publications
0
30
0
Order By: Relevance
“…A set of four bands were identified at ∼67, ∼55, ∼5, and ∼ 4 ppm 56 in the 27 Al NMR spectrum of nano-Al 2 O 3 support, which were readily assigned to four-, four-, six-and six-coordinated Al, respectively. 57,58 Significantly, the 27 Al NMR spectrum of 55%PEI@2%Al 2 O 3 appeared as a new signal at ∼34 ppm corresponding to the five-coordinated Al. 59 first transforms into a transition state, that is, the Lewis acid site is broken to form an acidic center (Al + ) and a basic center (O − ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A set of four bands were identified at ∼67, ∼55, ∼5, and ∼ 4 ppm 56 in the 27 Al NMR spectrum of nano-Al 2 O 3 support, which were readily assigned to four-, four-, six-and six-coordinated Al, respectively. 57,58 Significantly, the 27 Al NMR spectrum of 55%PEI@2%Al 2 O 3 appeared as a new signal at ∼34 ppm corresponding to the five-coordinated Al. 59 first transforms into a transition state, that is, the Lewis acid site is broken to form an acidic center (Al + ) and a basic center (O − ).…”
Section: Resultsmentioning
confidence: 98%
“…There was no additional overlapping band in 55%PEI@Commercial SiO 2 , indicating a small cross-linked reaction between PEI and commercial SiO 2 . A set of four bands were identified at ∼67, ∼55, ∼5, and ∼ 4 ppm in the 27 Al NMR spectrum of nano-Al 2 O 3 support, which were readily assigned to four-, four-, six- and six-coordinated Al, respectively. , Significantly, the 27 Al NMR spectrum of 55%PEI@2%Al 2 O 3 appeared as a new signal at ∼34 ppm corresponding to the five-coordinated Al . Fitzgerald et al have shown that the nano-Al 2 O 3 six-coordinated Al would transform into five-coordinated Al after adsorbing NH 3 via the surface Lewis acid sites.…”
Section: Resultsmentioning
confidence: 98%
“…investigated the thermal evolution of tetrahedral and pentahedral aluminum atoms in amorphous aluminum hydroxide fluorides with low degrees of fluorination. 15 Chupas et al studied the fluorination of γ-alumina (γ-Al2O3) with HCF2Cl and the formation of catalysts at high temperatures of 300 or 400 o C. 16 The application of 19 F/ 27 Al CP-MAS NMR techniques demonstrated that changes due to low levels of fluorination on the surface of the alumina could be studied by this technique. 16 Dando used 19 F solidstate NMR to study the fluoride adsorption mechanism in smelting grade alumina (SGA).…”
Section: Solid-state Mas Nmr Of Fluoraluminate Materialsmentioning
confidence: 99%
“…The aim of this work was to synthesize a series of gibbsite specimens calcined at various temperatures and explore how the temperature affects the adsorption properties of corresponding aluminas and what impact the fluorination process has on local aluminum coordination. Therefore, XRD on the gibbsite calcined at various temperatures and 27 Al MAS NMR, 19 F- 27 Al CP-MAS and 19 F MAS NMR solid-state NMR measurements on these and related HF adsorption products were performed to analyze the process of low-level fluorination.…”
Section: Solid-state Mas Nmr Of Fluoraluminate Materialsmentioning
confidence: 99%
“…[5] Fluorination of -Al2O3-700 with CHClF2 also gives a highly Lewisacidic mesoporous catalyst. [6] In the presence of Et3SiH dehydrofluorination of fluoropentane was found, albeit with very low selectivity. A Nb doped Al hydroxide fluoride was obtained by reaction of Al isopropoxide with aqueous HF, and post-fluorination of the produced xerogel with CHClF2 at higher temperatures.…”
mentioning
confidence: 98%